ANALISIS DAMPAK MERGER DAN AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEITAHUN 2007-2010 (Students' Journal of Accounting and Banking, 2014)
This study analyzes the impact of mergers and acquisitions on the financial performance of non-financial companies listed on the Stock Exchange in 2007-2010. This research was conducted at the Indonesian Stock Exchange by using the unit of analysis of non financial companies that have go public. The sampling method used purposive sampling with the period of the study in 2007-2010. The purpose of this study was to determine the changes in the company's financial performance before and after mergers and acquisitions. Measurement of company performance measured by financial ratios include the Current Ratio, Total Asset Turn Over, Debt To Equity Ratio, Net Profit Margin, Return On Investment, Return On Equity and Earnings Per Share. Analyses were performed using the Wilcoxon Signed Ranks Test. The results show that financial performance is measured by the Current Ratio, Total Asset Turn Over, Debt To Equity Ratio, Net Profit Margin, Return on Investment, Return on Equity and Earnings Per Share shows no significant difference between before and after mergers and acquisitions. Keywords: Mergers, Acquisitions, Financial Performance